(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Essential hypertension is associated with altered pulmonary function. Antihypertensive medication and lung function are also associated. Losartan (angiotensin II receptor blocker) and amlodipine (calcium channel blocker) are commonly used antihypertensive drugs. Objectives: To evaluate the effects of antihypertensive drugs on lung function status in patients with essential hypertension. Materials and Methods: This prospective observational study was carried out in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, from July 2012 to June 2013 on 100 newly diagnosed hypertensive patients without any antihypertensive medication (group B, age 30-55 years). They were selected from the Out Patient Department (OPD) of Cardiology, BSMMU, Dhaka. Age, sex and BMI matched 50 apparently healthy normotensive subjects were also studied as control (group A). Based on treatment, these study subjects were divided into two groups (B1 and B2). Group B1 included 50 patients received losartan 50 mg daily and B2 included 50 patients received amlodipine 5 mg daily. They were observed once before the treatment (B1a and B2a), after 3 months of medication (B1b and B2b) and after 6 months of medication (B1c and B2c). For assessing lung function status, Forced Vital Capacity (FVC), Forced Expiratory Volume in 1st second (FEV1) and Peak Expiratory Flow Rate (PEFR) were measured with a RMS computer based Spirometer. Results: Mean FVC, FEV1 and PEFR were significantly lower in newly diagnosed hypertensive patients in comparison with that of healthy normotensive. Mean FVC, FEV1 and PEFR were found significantly higher in the group taking losartan and amlodipine for 6 months when compared to newly diagnosed but lower than those of controls. Conclusion: Reduced lung function occurs in newly diagnosed hypertensive patients which was improved by treatment with losartan and amlodipine. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 42-44